2022
DOI: 10.3390/ijerph192114341
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Analysis of Attrition in Parent–Child Interaction Therapy

Abstract: Parent–child interaction therapy (PCIT) is one of the strongest evidence-based treatments for young children with behavior problems. Despite the efficacy of PCIT, many families fail to complete treatment, with attrition rates ranging from 30 to 69 percent. Preliminary research on attrition in PCIT treatment studies has linked maternal distress, negative verbal behavior (critical and sarcastic comments towards the child), lower socioeconomic status (SES), and fewer child major depressive disorder (MDD) diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…High attrition rates, recorded to be between 30% to 69% in PCIT programs 115 have instigated modifying standard PCIT to more brief versions with less time investment, but with similar effectiveness. Increasingly practitioners are realizing that the intensive support and skill practice provided for up to 16 weeks of PCIT may be overservicing some families.…”
Section: Current Research On Standard Pcit Generalizability and Mecha...mentioning
confidence: 99%
“…High attrition rates, recorded to be between 30% to 69% in PCIT programs 115 have instigated modifying standard PCIT to more brief versions with less time investment, but with similar effectiveness. Increasingly practitioners are realizing that the intensive support and skill practice provided for up to 16 weeks of PCIT may be overservicing some families.…”
Section: Current Research On Standard Pcit Generalizability and Mecha...mentioning
confidence: 99%
“…That is, parents were instructed to perform each PRIDE skill five times during rehearsal for each training session. Although typical PCIT mastery criteria are implementation of each skill 10 times during a 5-min session (Eyberg & Funderburk, 2022), we set a goal of five per session as high mastery criteria have previously led to treatment attrition (Ufford et al, 2022). The lead clinician provided feedback for whether parents met our study's mastery criteria for each skill, with specific examples and recommendations for meeting criteria during future play sessions.…”
Section: Baselinementioning
confidence: 99%
“…Research indicates that some parents may require as many as 24 sessions to meet strict PCIT mastery criteria (Goldfine et al., 2008). As a result, attrition in PCIT research varies widely and has been reported as high as 67% in some studies (Fernandez & Eyberg, 2009; Lieneman et al., 2019; Lyon & Budd, 2010; Ufford et al., 2022). Moreover, attrition may be particularly high for underrepresented and low‐SES families (Lieneman et al., 2019; Lyon & Budd, 2010; Werba et al., 2006).…”
Section: Introductionmentioning
confidence: 99%